Cognitive Education in the Elderly with Guess the Objects Game At Tresna Werda Husnul Khotimah Social Institution - Chairil, Chairil; Sita Dewi; Rinda Nisra (Jurnal Pengabdian UntukMu NegeRI, 2024)
Elderly experience changes in the function of body systems, one of which is a decrease in cognitive function. Group activity therapy is a type of therapy modality that can be made by nurses in an elderly group to improve cognitive function in the elderly. Guess objects is one of the options for group activity therapy in the elderly that improves cognitive function. The purpose of the implementation of this guessing group activity therapy activity is to improve cognitive function in the elderly at the Tresna Werda Husnul Khotimah Social Institution, Riau ProvinceThe participants of this activity were elderly at Wisma Dahlia which amounted to 5 people The methods used in this activity were lectures, demonstrations and discussions. The results of the activity showed that the elderly were actively and enthusiastically involved in this activity and could guess objects 3and 2 who can't guess correctly. It can be concluded that this activity can help in improving cognitive function in the elderly through group activity therapy guessing objects